A randomized controlled trial of lycopene treatment on soluble receptor for advanced glycation end products in seminal and blood plasma of normospermic men - Oborná, Ivana; Černá, Karin; Fingerová, Helena; Březinová, Jana; Horká, Petra; Novotný, Jiří; Bryndová, Hana; Filipčíková, Radka; Svobodová, Magda (American journal of reproductive immunology, 2011)
PROBLEM: The aim of present study was to investigate the effects of antioxidant lycopene on soluble receptor for advanced glycation end products (sRAGE) levels in blood and seminal plasma in normospermic males. METHODS: Study included 15 fertile volunteers and 13 normospermic male partners from infertile relationships. The treatment was 12-week administration of 20 mg of lycopene or placebo followed by crossover and treatment for a further 12 weeks. The ELISA kit Quantikine(®) was used to determine sRAGE levels. RESULTS: Lycopene administration decreased sRAGE levels in seminal plasma in fertile volunteers (controls) as well as in male partners in the infertile relationships group (P=0.008 and P=0.012, respectively). No significant effect of lycopene on sRAGE in blood plasma was found in either group, but seminal plasma sRAGE was significantly suppressed. CONCLUSION: Lycopene decreased sRAGE in seminal, but not in blood plasma. This may be because of selective local uptake of lycopene in the male reproductive tract, namely in prostate. Decreased sRAGE may be caused by lycopene suppression of oxidative stressors and explain in part the putative improvement in fertility reported after lycopene treatment.
Keywords: Carotenoids; sperma; lidé; Prostate; Receptors, Immunologic; Biomarkers; Humans; Semen; karotenoidy; biologické markery; mužské pohlaví; Male; receptory imunologické; prostata